Comparative analysis of the effectiveness of modern irrigants activation techniques in the protocol of chemomechanical root canal system treatment (literature review) - Potapchuk Анатолій Мефодійович; Almashi Василь Миколайович; Rak Юрій Володимирович; Melnyk Юрій Олексійович; Buleza Віктор Валерійович; Horzov Арсеній Петрович (Actual Dentistry, 2023)
Resume. Development of apical periodontitis is the most common complication of unsuccessful endodontic treatment. Cleaning the root canal system is a crucial stage and the main factor for a successful endodontic protocol. Inability to remove debris from inaccessible branches of the root canal system, especially from the apical region, leads to and increases the risk of secondary infection. Selection of the optimal method for activating irrigants remains a current issue. According to the results of several studies, none of the individual irrigation activation techniques allows achieving ideal cleanliness in the root canal, but the use of laser, sonic, multisonic, and ultrasonic activation significantly improves the quality of cleaning and provides a prolonged antimicrobial effect by enhancing the diffusion of intracanal antiseptics, their hydrolytic and antibacterial effectiveness, which will eventually ensure maximum adhesion of filling materials. This, in turn, indicates the absence of a unified protocol that would provide stable irrigation efficiency and long-term results in endodontic treatment. The use of a protocol with combined activation of irrigants remains an open question among clinicians and scientists.